Bridges for Kansas families: the role of social capital and hardiness in alleviating poverty. - Cless, Adam W. (Kansas State University, 2017)
For the past decade, family poverty has been growing steadily by 24.3% within the state of Kansas. The increase in poverty has inspired community-based efforts and volunteer-driven initiatives to grow to support families and to increase social connection and access to resources. Prior research has found that families in chronic poverty experience higher stress, higher conflict, and lower means of social connection. In the present study, a Community-based Participatory Research (CBPR) approach was used to explore the "lived experiences" of parents and adolescents in poverty and the role of social capital and hardiness as a way to cope with the stresses associated with living in poverty. Separate semi-structured interviews were conducted with adolescents and their adult parents from three communities across Kansas. The research team transcribed the interview data. Qualitative data analysis through grounded theory was used to code the transcripts into separate themes. The results from the study reveal that a) building social capital (ie., bonding and bridging) is different between adolescents and parents and b) hardiness is developed through learned positive coping and the social connections with others. This research has future implications on policy development and strengths-based approaches to address the stress of living in poverty for individuals and families.
Keywords: social capital; hardiness; adaptation; qualitative analysisfamily poverty